2022
DOI: 10.3390/crops2030021
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Content, Phytochemical Profiling, and Physical Properties of Buckwheat (Fagopyrum esculentum) Seeds for Promotion of Dietary and Food Ingredient Biodiversity

Abstract: The adoption of food crops as a source of dietary macro- and micro-nutrients is a sustainable way to promote diet biodiversity and health while being respectful to the environment. The aim of this work was to comprehensively characterize the nutrient and phytochemical content of buckwheat seeds (Fagopyrum esculentum) and assess their physical properties for the evaluation of their suitability as food ingredients. The buckwheat samples were found to be complete sources of amino acids (UPLC-TUV analysis), with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The protein content was determined by environmental conditions to the greatest extent among all the tested features at the level of 84.7%, and the share of G × E interactions was 12.8% (Table 2). There was no effect of genotype on the content of this component, although some literature data show such a relationship 21,22 . Studies described by other authors 7,17,20 confirmed the high significant influence of place of cultivation as well as the growing season on the amount of protein in common buckwheat grains.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The protein content was determined by environmental conditions to the greatest extent among all the tested features at the level of 84.7%, and the share of G × E interactions was 12.8% (Table 2). There was no effect of genotype on the content of this component, although some literature data show such a relationship 21,22 . Studies described by other authors 7,17,20 confirmed the high significant influence of place of cultivation as well as the growing season on the amount of protein in common buckwheat grains.…”
Section: Resultsmentioning
confidence: 51%
“…There was no effect of genotype on the content of this component, although some literature data show such a relationship. 21,22 Studies described by other authors 7,17,20 confirmed the high significant influence of place of cultivation as well as the growing season on the amount of protein in common buckwheat grains. There were no significant differences in the ash content in grains between analyzed common buckwheat cultivars with average level of 24 g kg −1 that is consistent with the values presented in the literature.…”
Section: Yield and Nutrientsmentioning
confidence: 62%
“…The buckwheat dietary fibre is concentrated in the hull; 100 g of hulled buckwheat contributes up to half the daily dietary recommendation for fibre as NSP [ 10 ] , with the majority of the NSP being in the insoluble form. Although hulled buckwheat has a similar monomeric structure composition to wheat bran, the ratio between the monomers differs.…”
Section: Broad Beans Buckwheat and Hemp As Alternatives Sources Of Nu...mentioning
confidence: 99%
“…Buckwheat could contribute to delivering the recommended nutrient intake for several minerals; 100 g of buckwheat could deliver 83% of the daily reference nutrient intake (RNI) for magnesium, 78% for phosphorus, 40% for iron, 48% for zinc, 50% for copper, 88% for molybdenum, and the daily RNI for manganese and chrome, as well as being a rich source of calcium and iron [ 10 ] . Nutritional studies should establish the bioavailability of buckwheat microelements and further explore their potential as functional ingredients for food fortification to tackle malnutrition.…”
Section: Broad Beans Buckwheat and Hemp As Alternatives Sources Of Nu...mentioning
confidence: 99%